Performance of stochastic targeted blood glucose control protocol by virtual trials in the Malaysian intensive care unit - Ummu Kulthum, Jamaludin; Fatanah, M. Suhaimi; Normy Norfiza, A. Razak; Azrina, Md Ralib; Mohd Basri, Mat Nor; Pretty, Christopher G.; Luqman, Humaidi (Elsevier Ireland Ltd, 2018)
Blood glucose variability is common in healthcare and it is not related or inﬂu- enced by diabetes mellitus. To minimise the risk of high blood glucose in critically ill patients, Stochastic Targeted Blood Glucose Control Protocol is used in intensive care unit at hospitals worldwide. Thus, this study focuses on the performance of stochastic modelling protocol in comparison to the current blood glucose management protocols in the Malaysian intensive care unit. Also, this study is to assess the ef- fectiveness of Stochastic Targeted Blood Glucose Control Protocol when it is applied to a cohort of diabetic patients.